2021
DOI: 10.1111/vco.12692
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immunohistochemical markers in canine cutaneous mast cell tumours: A systematic review and meta‐analysis

Abstract: Histological grading systems remain cornerstones in the prognosis of canine cutaneous mast cell tumours (MCTs), but the distinct biological behaviour of each tumour often necessitates the use of complementary markers. Although a plethora of immunohistochemical markers have been proposed as prognostic factors, few are presently applied in routine diagnosis. This systematic review and meta‐analysis was designed to establish which immunohistochemical markers have verifiable prognostic value for cutaneous MCTs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…However, in the study by Scase and colleagues [ 107 ], although AgNOR and Ki-67 levels had prognostic value, PCNA expression showed no correlation with prognosis. Freytag et al [ 146 ] carried out an extensive review and meta-analysis aiming to identify the immunohistochemical markers that have the greatest prognostic value in this context to date. They observed that Ki-67 and KIT expression have prognostic value, and the pro-apoptotic immunomarker BAX also showed promising application as a prognostic factor in MCTs.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…However, in the study by Scase and colleagues [ 107 ], although AgNOR and Ki-67 levels had prognostic value, PCNA expression showed no correlation with prognosis. Freytag et al [ 146 ] carried out an extensive review and meta-analysis aiming to identify the immunohistochemical markers that have the greatest prognostic value in this context to date. They observed that Ki-67 and KIT expression have prognostic value, and the pro-apoptotic immunomarker BAX also showed promising application as a prognostic factor in MCTs.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Mast cell tumors (MCTs) are the most common skin tumor affecting dogs, and the tumor grade is the most consistent and clinically relevant prognostic factor [1][2][3][4]. There are two MCT grading systems: the Patnaik system and the Kiupel system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ki67 is a nuclear protein that is expressed in all phases of the cell cycle except G0 and represents the tumor growth fraction. The relative number of cells expressing Ki67 is an established prognostic factor in canine MCTs and other malignancies in several species [2,11]. There are multiple variants of Ki67, with species, cell-type, and cell-cycle specificity, and it forms the perichromosomal layer during mitosis, preventing chromosomes from sticking together and maintaining chromosomal structural integrity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations